Effects of the simulated drift of ripeners on Eucalyptus urograndis - Pires, Rodrigo Neto [UNESP]; Pereira, Fernanda Campos Mastrotti [UNESP]; Nepomuceno, Mariluce Pascoina [UNESP]; Da Costa Aguiar Alves, Pedro Luis [UNESP] (Canadian Center of Science and Education, 2013)
The objective of this study was to evaluate the effects of the drift of ripeners (sulfometuron-methyl, ethephon and trinexapac-ethyl) on the initial growth of Eucalyptus urograndis. The experimental design was a randomized block with seven treatments (control; sulfometuron-methyl 0.9 and 1.2 g i.a. ha-1; ethephon 28.8 and 38.3 g i.a ha-1; trinexapac-ethyl 15 and 20 g i.a. ha-1) with four replicates using each plant as an experimental plot. We evaluated the effects 7, 14, 21, 28, 35 and 42 days after application, when we determined the length, diameter, total leaf area and total dry mass of the stem. The application of sulfometuron-methyl may have resulted in an effect known as hormesis due to an increasing trend in stem growth. The application of trinexapac-ethyl resulted in greater increases in the leaf dry mass and leaf area compared with those caused by the other ripeners that were used in this study, most likely due to the loss of apical dominance. The application of ethephon had no significant effect on the plants.
Keywords: Ethephon; Hormesis; Sulfometuron-methyl; Trinexapac-ethyl